Strategies and Approaches to Early Literacy Learning for Early Childhood - prasasti, Oka; Formen, Ali; Mulyani, Petra Kristi (Advances In Social Humanities Research, 2025)
Language development in early childhood is greatly influenced by optimal early literacy stimulation from preschool age. Early literacy forms a crucial foundation for reading, writing, communication skills, and children's confidence. This study analyzes strategies and approaches in early literacy learning to enhance language skills at Al Irsyad Al Islamiyyah Kindergarten Pemalang. It employs a qualitative case study method, with data gathered via observation, interviews, and documentation, validated through source triangulation. Analysis followed the Miles and Huberman model: data reduction, presentation, and conclusion drawing. Results revealed that educators' early literacy strategies—playing, singing, and storytelling—effectively stimulate interest, enrich vocabulary, and familiarize children with letters, numbers, shapes, and colors in engaging ways. Applied approaches included behaviorism, cognitive, and social constructs, providing language stimulation while emphasizing social interactions with the environment. These complementary strategies and approaches foster active, creative, participatory learning environments, significantly advancing children's language development. Thus, the study confirms that early literacy success hinges on educators selecting strategies aligned with early childhood needs and developmental stages.